Rhino-orbital-cerebral mucormycosis in a pediatric cancer patient - Couto, Maria Eduarda (2021)
Aim: Mucormycosis infections are highly lethal in immunosuppressed patients. The authors present a rare case of successful treatment of the condition. Case description: A 14-year-old male with acute lymphoblastic lymphoma in remission was diagnosed with pansinusitis, cerebral osteomyelitis, and encephalitis with an abscess caused by Rhizopus sp. Neurosurgical drainage, endoscopic sinus surgery, and left eye enucleation were performed, and the patient was simultaneously treated with lipossomal-amphotericin B and posaconazol (later replaced by isavuconazol). However, complications (left frontal lobe herniation and cerebrospinal fluid fistula) ensued, requiring surgical reoperation. Chemotherapy was restarted four months later. Comments: This is a rare case report, in which early and aggressive surgery, antifungal treatment, and multidisciplinary team work were crucial for the successful outcome.